Penilaian Multi Bahaya Pesisir di Daerah Muara Sungai Randangan, Teluk Tomini, Indonesia - Djuraini, Moh. Fahry (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2025)
This study aims to provide a preliminary assessment of coastal hazards in the Randangan River Mouth Coastline, Tomini Bay, Indonesia, using the Coastal Hazard Wheel (CHW) framework. The assessment focuses on key parameters such as geomorphology, wave exposure, tidal range, vegetation cover, sediment balance, and storm climate across a 14.46 km coastal stretch. Results reveal high levels of vulnerability, with ecosystem disruption, gradual inundation, and coastal erosion each posing very high to high risks along 8.35 km of the coastline, particularly in sediment plains and deltaic zones with minimal vegetation. Saltwater intrusion affects nearly the entire coastline (13.91 km) at moderate risk, while flooding presents a high risk across 13.54 km, indicating the limited buffering capacity of existing natural features. Despite data limitations, the CHW approach effectively identifies and maps multi-hazard exposure, providing a valuable tool for early-stage planning. The findings underscore the need for integrated coastal zone management, including ecosystem-based interventions and improved data collection, to support long-term resilience and adaptive strategies in vulnerable coastal settings.